(untitled) (Indian Journal of Arid Horticulture, 2025)
The nutritional survey conducted on aonla fruit orchards at different locations in Chittorgarh district of Rajasthan. Variation observed for quality parameters of aonla fruits in different locations. The soil nutrient status influences the quality parameters of the fruits. The average fruit weight of aonla varied from 32.71 to 38.40 g per fruit with the mean value of 35.68 g/fruit. The pooled average fruit length and fruit breadth varied 3.11 to 3.41 cm and 3.79 to 4.15 cm, respectively. The pooled stone weight varied from 1.89 to 2.05 g and pulp to stone ratio ranged from 17.30 to 18.74. The fruit yield per tree ranged from 54.88 to 71.43 kg plant. The total soluble solids content ranged from 10.76 to 11.78° Brix and total acidity was recorded between 1.85 to 1.93 per cent. The TSS/acid ratio, ascorbic acid contents, total sugar and reducing sugars varied from 5.58 to 6.35, 411.65 to 581.50 mg/100 g pulp, 4.97 to 6.28% and 1.71 to 2.10%, respectively. The quality parameters is found to be directly related to soil nutrient status, hence, better nutrition is likely to improve the quality parameters of aonla fruits.